Subacute hypersensitivity pneumonitis in an HIV infected patient receiving antiretroviral therapy. Issue 7 (1st July 2000) - Morris, Alison M; Nishimura, Stephen; Huang, Laurence
Abstract : Abnormal pulmonary immune response to various antigens can lead to hypersensitivity pneumonitis. This disease has not previously been reported in HIV infected patients. This case report describes an HIV infected woman who developed subacute hypersensitivity pneumonitis in response to bird exposure. The disease manifested itself only after the patient experienced an improvement in her CD4 positive T lymphocyte count secondary to antiretroviral therapy. This case emphasises the need to consider non-HIV associated diseases in patients with HIV and suggests that diseases in which host immune response plays an essential role in pathogenesis may become more prevalent in HIV infected patients receiving effective antiretroviral therapy.